1982
DOI: 10.3109/00207458208985916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcohol Ingestion on Regional Cerebral Blood Flow

Abstract: Regional distribution of cerebral blood flow was assessed in 10 normal social drinkers following consumption of .75 g/kg alcohol and in a control session without alcohol. Alcohol increased blood flow in the gray matter in all brain areas except the left anterior area. The results are discussed in terms of the effect of alcohol on regional cerebral activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Investigators have found decreased rCBF in cerebellum and increased rCBF in the parietal and prefrontal cortex (Volkow et al, 1990), increased rCBF in the frontal cortex only (Matthew and Wilson, 1986), increased rCBF in the right prefrontal cortex (Tiihonen et al, 1994), and increased rCBF in all gray matter areas except the left anterior cortical areas (Newlin et al, 1982). Decreased CMRglu was found in frontal cortices (De Wit et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have found decreased rCBF in cerebellum and increased rCBF in the parietal and prefrontal cortex (Volkow et al, 1990), increased rCBF in the frontal cortex only (Matthew and Wilson, 1986), increased rCBF in the right prefrontal cortex (Tiihonen et al, 1994), and increased rCBF in all gray matter areas except the left anterior cortical areas (Newlin et al, 1982). Decreased CMRglu was found in frontal cortices (De Wit et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations of normal, healthy subjects have revealed that moderate ethanol inebriation is followed by a global increase in cerebral blood flow (CBF) during rest (Mathew & Wilson, 1986;Newlin, Golden, Quaife, & Graber, 1982;Sano et al, 1993). Most likely this is caused by a global vasodilatatory effect of ethanol (Greenberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The changes were most obvious in the frontal areas. Newlin and associates 20 also reported more marked post-ethanol CBF increase in the frontal regions. However, unlike their findings, in the present study there were no significant interhemispheric differences in the flow change.…”
Section: Discussionmentioning
confidence: 85%
“…However, during severe alcohol intoxication with high blood levels (.32 mg/percent) there was a pronounced increase in cerebral blood flow and reduction in cerebral vascular resistance and oxygen uptake. More recently, Newlin and associates 20 studied the effects of ethanol on CBF with the '"Xenon inhalation technique in 10 social drinkers. CBF was measured one hour after the oral administration of .75 g per kg body weight of alcohol.…”
mentioning
confidence: 99%